2022
DOI: 10.3390/antibiotics11040444
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Escherichia coli from the Broiler Farm Environment, with Detection of SHV-12-Producing Isolates

Abstract: Antimicrobial resistance is an important One Health challenge that encompasses the human, animal, and environmental fields. A total of 111 Escherichia coli isolates previously recovered from manure (n = 57) and indoor air (n = 54) samples from a broiler farm were analyzed to determine their phenotypes and genotypes of antimicrobial resistance and integron characterization; in addition, plasmid replicon analysis and molecular typing were performed in extended-spectrum-beta-lactamase (ESBL) producer isolates. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
1
10
1
Order By: Relevance
“…Interestingly, all five strains of E. coli were resistant to trimethoprim/sulfamethoxazole. The previous studies reported trimethoprim/sulfamethoxazole-resistant E. coli isolates from broiler chickens in many countries such as Canada, Bangladesh, and Spain [46][47][48], including Thailand [48]. Mooljuntee et al [49] reported that 26.7% of trimethoprim/sulfamethoxazole-resistant E. coli were found in broiler chickens, while our study reported 21.74%.…”
Section: Discussioncontrasting
confidence: 58%
“…Interestingly, all five strains of E. coli were resistant to trimethoprim/sulfamethoxazole. The previous studies reported trimethoprim/sulfamethoxazole-resistant E. coli isolates from broiler chickens in many countries such as Canada, Bangladesh, and Spain [46][47][48], including Thailand [48]. Mooljuntee et al [49] reported that 26.7% of trimethoprim/sulfamethoxazole-resistant E. coli were found in broiler chickens, while our study reported 21.74%.…”
Section: Discussioncontrasting
confidence: 58%
“…Colibacillosis is the leading cause of mortality (up to 20%) in the poultry industry and its prevalence is up to 36.7% [ 12 , 36 ]. Antibiotics are used to treat poultry colibacillosis cases, especially in the first week of life when the immune system of the animals is not fully developed [ 37 ]. MDR E. coli strains are a major problem, as due to the high variability observed, E. coli outbreaks happen on the same farm despite the massive use of antibiotics [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite their control, the rate of resistance to certain classes of antibiotics continues to rise [ 40 ] and different studies have demonstrated the close association between animal products and humans [ 21 , 22 , 23 , 24 , 25 , 26 ]. Therefore, for a long time, AMR has been centered on the clinical field, but currently it is widely recognized as a problem that affects human, animals, and the environment, which needs to be addressed from a One Health approach [ 37 ]. In fact, the overall analysis performed of antibiotic consumption and resistance, both in humans compared to humans, animal compared to animal and animal compared to human, shows the existence of positive correlations between antibiotic consumption and resistance rates, with a maximum for animal compared to animal and a minimum for animal compared to human.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO has declared antimicrobial resistance to be one of the 10th greatest public health threats facing humanity [ 2 ]. The lack of new drug development as well as the misuse and overuse of antimicrobials remains the main factors that have led to the rise and spread of drug-resistant pathogens, which has slowed down the eradication process of infectious diseases [ 3 ]. Antibiotic resistance has gradually developed and now affects all pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%